(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The section discusses the social role of women in colonial India. In this paper I tried to stress that women’s role is a social system and defines their interaction with others. In this segment, I have tried, with a series of instances, in particular practices, to explore the prevalent social structures, which paint a multi-layered image of the woman’s social dynamics and expose the complicated systemic arrangements in society regarding women’s status. The explanations for the low status of women in India have been the presence of social evils such as satiety, child marriage, slavery, compulsory widowhood, lack of schooling, purdah method etc. In this background, I also tried to illustrate why, in different areas and cultures, the role of women differs from community to community in various geographies and from tribal to caste-oriented communities.